THE ANALYSIS OF ENGLISH LEARNING STYLES OF GRADE 10 STUDENTS IN THE CONTEXT OF IMPLEMENTING THE MERDEKA CURRICULUM AT SMA N 1 KINTAMANI - I Komang Angga Sila Dharma; Luh Made Dwi Wedayanthi; Pande Agus Adiwijaya (Jurnal Genta Mulia, 2024)
This study aims to determine the learning style of grade 10 H students at SMA N 1 Kintamani in implementing the Merdeka Curriculum. This research was conducted using a qualitative approach and a case study method. This research was conducted at SMA N 1 Kintamani with 37 students. Research data were collected through questionnaires, interviews, observation and documentation. Data analysis uses techniques from Miles and Huberman, namely collecting, reducing, presenting, and drawing conclusions. The results of this study show that the learning style of class 10 H students was dominated by the Kinesthetic learning style of 43% with a total of 16 students. Kinesthetic learning style was at 41% with 15 students. Meanwhile, the Read / Write learning style was at 11% with 4 students, and the Visual Learning Style was at 5% with 2 students. In implementing the independent curriculum, teachers should conduct initial diagnostic tests and provide a differentiated learning process.